2015
DOI: 10.1093/mnras/stv1628
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of silicate surface morphology in interstellar H2formation. Insights from quantum chemical calculations

Abstract: The adsorption of H atoms and their recombination to form an H 2 molecule on slab models of the crystalline Mg 2 SiO 4 forsterite (001) and (110) surfaces was studied by means of quantum mechanical calculations based on periodic density functional theory (DFT). Present results are compared with those previously reported for the most stable (010) surface, showing the relevance of the surface morphology and their stability on the H 2 formation. Different H chemisorption states were identified, mostly on the oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…When compared to other siliceous models with the Mg−Si−O centers involved in the H 2 synthesis, the Fe‐POSS system favorably shifts all the energies (from thermodynamic potentials to barrierless kinetics) toward the H 2 formation because of the Fe catalytic center.…”
Section: Figurementioning
confidence: 96%
See 4 more Smart Citations
“…When compared to other siliceous models with the Mg−Si−O centers involved in the H 2 synthesis, the Fe‐POSS system favorably shifts all the energies (from thermodynamic potentials to barrierless kinetics) toward the H 2 formation because of the Fe catalytic center.…”
Section: Figurementioning
confidence: 96%
“…Though not receiving the same attention as ice and carbonaceous‐based surfaces, the theoretical analysis of siliceous surfaces like crystalline Mg 2 SiO 4 ( forsterite ), Fe 2 SiO 4 ( fayalite ), olivine and Mg‐silicates nano‐clusters has been considered . The net results showed that although H 2 formation is possible, reaction mechanisms are a function of the crystalline surfaces (001, 010, 110), atoms and defects (metal cation vacancies) where the adsorption/reaction sites are placed …”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations